New challenges of modernity for Ukrainian tourist industry (compliance program within the framework of logistics management in the conditions of crisis) - Garmash, Sergii; Pererva, Petro (Management and Entrepreneurship: Trends of Development, 2020)
It should be noted that the global financial crisis of 2008, which affected all spheres of people’s livelihoods, pushed the development of the tourist industry. Governments in many countries have begun to pay more attention to this market segment, as it is this segment that is able to restore its position and profit in a relatively short time. Another situation is with the COVID-19 pandemic. When “deferred opportunities” turn into “lost opportunities”. The aim of the research is summarizing the experience of travel companies in overcoming the negative consequences of crisis situations; tracking the typical trends of the behavior of travel companies in the market for the provision of travel services in such situations and development of practical recommendations for the possible use of a compliance program at a travel company as a part of logistics management. Methodology: while working at the article, the following methods of scientific knowledge were used: the method of unity of analysis and synthesis, method of expert assessments, comparative analysis and systemic approach. Scientific novelty: the implementation of a compliance program at a travel company organically fits into the logistics management system. Practical value: the effects of the global economic crisis due to COVID-19 pandemic and the quarantine have yet to be understood. Many domestic travel companies, referring to force majeure, impose penalties on their customers. In order to prevent corruption in such crisis conditions, it is necessary to introduce compliance programs within the travel industry in the framework of logistics management. This will help to meet the needs of the client as well as the development of the travel company even in times of crisis.JEL Classification: E20, L83, M21.